A case of urinary incontinence by hydroxychloroquine in a geriatric patient. (29th November 2012) - Carnovale, C.; Perrone, V.; Borsadoli, C.; Mambrini, A.; Speziali, A.; Froldi, G.; Antoniazzi, S.; Magistro, L.; Clementi, E.; Radice, S.
Summary: What is known and Objective: Rheumatoid arthritis is an autoimmune disorder characterized by persistent synovitis and systemic inflammation. Genetic factors account for approximately 50% of cases of rheumatoid arthritis and environmental factors include smoking. Urinary incontinence may occur as a medication adverse effect. We present the first report of a case of hydroxychloroquine‐induced urinary incontinence in rheumatoid arthritis. Details of the case: A 71‐year‐old female with a history of rheumatoid arthritis developed urinary incontinence as an adverse drug reaction to hydroxychloroquine administered at therapeutic doses. Urinary incontinence remitted with drug withdrawal and reappeared on rechallenge. The Naranjo's algorithm indicated that hydroxychloroquine was a probable cause of this adverse drug reaction. The likely mechanism of this adverse drug is a direct action of the quinolone on the urinary system. What is new and conclusion: This is the first report of hydroxychloroquine‐induced urinary incontinence. The absence of previous reports suggest that the drug rarely causes this adverse effect. Methotrexate is most often used as first‐line treatment, and several other drugs are now available to act as Disease‐Modifying Antirheumatic Drugs (DMARDs). These drugs may be used alone or combined with methotrexate, most often to increase efficacy and reduce toxicity. The introduction of new biological agents, such as abatacept, rituximab, tocilizumab and inhibitors of tumour necrosis factor, has opened new therapeutic perspectives but are restricted by high costs and risk of infections. Thus, antimalarial drugs, especially the quinolones chloroquine (CQ) and hydroxychloroquine (HCQ), are still in use, and the latter is very efficacious. An advantage of HCQ is its low toxicity compared with other antimalarial drugs. Common side‐effects of HCQ and the other antimalarial drugs include gastrointestinal effects such as nausea and vomiting, as well as skin rashes and headache, whereas their most common and severe side‐effect is retinopathy. No case of urinopathy has been reported previously with HCQ.